1983
DOI: 10.1002/pol.1983.170210409
|View full text |Cite
|
Sign up to set email alerts
|

Friedel–crafts crosslinking methods for polystyrene modification. IV. Macromolecular structure of crosslinked particles

Abstract: Crosslinked polystyrene particles were prepared by Friedel–Crafts suspension crosslinking of polystyrene using 2,4‐dichloromethyl‐2,5‐dimethyl benzene as crosslinking agent. The polymer was dissolved in nitrobenzene and reaction occurred in a 70 wt % aqueous solution of ZnCl2 with poly(vinyl alcohol) as a suspending agent. The spherical particles produced were swollen in toluene, chloroform, and tetrahydrofuran to determine their equilbrium polystyrene volume fraction. Analysis of the crosslinked macromolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…An emulsion with water could not form due to sensitivity of the catalyst to water. Friedel–Crafts alkylation is optimal for functionalizing phenyl groups and was thus selected for cross‐linking the i PS chains . Prior to utilization in emulsion the process was tested for applicability with isotactic oligostyrene, poly(styrene), and poly(diphenyl‐ethylstyrene) (poly(DPES)) (see Chapter S‐III ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An emulsion with water could not form due to sensitivity of the catalyst to water. Friedel–Crafts alkylation is optimal for functionalizing phenyl groups and was thus selected for cross‐linking the i PS chains . Prior to utilization in emulsion the process was tested for applicability with isotactic oligostyrene, poly(styrene), and poly(diphenyl‐ethylstyrene) (poly(DPES)) (see Chapter S‐III ).…”
Section: Resultsmentioning
confidence: 99%
“…Friedel-Crafts alkylation is optimal for functionalizing phenyl groups and was thus selected for cross-linking the iPS chains. [16][17][18][19] Prior to utilization in emulsion the process was tested for applicability with isotactic oligostyrene, poly(styrene), and poly(diphenylethylstyrene) (poly(DPES)) (see Chapter S-III). These investigations showed that both poly(styrene) and poly(DPES) can be chemically cross-linked by Friedel-Crafts alkylation.…”
Section: Synthesis Of Ips Microgelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A crosslinked polymer is insoluble in methanol but swells with methanol by the suppression of elasticity due to network structures. In the swelling equilibrium state, the following modified Flory-Rehner's equation is valid [38,39],…”
Section: 5 Preparation Of Cross-linked Films Of Ptas With P P'-bmentioning
confidence: 99%